1969
DOI: 10.1172/jci106190
|View full text |Cite
|
Sign up to set email alerts
|

Decreased myocardial adenyl cyclase activity in hypothyroidism

Abstract: A B S T R A C T It has been suggested that hypothyroidism may alter the responsiveness of the heart to sympathetic stimulation. To define more precisely the interrelationship between hypothyroidism and catecholamine responsiveness we: (a) studied the effects of norepinephrine and fluoride on the activation of adenyl cyclase in the particulate fraction of heart homogenates from euthyroid and hypothyroid cats; and (b) assessed the contractile response of isolated right ventricular papillary muscles from the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1971
1971
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…In fact, diminished 1-receptor binding (with no change in affinity) during hypothyroidism has been demonstrated (3,15). In peripheral tissues, parallel changes in adenylate cyclase activity have been reported (16). Our electrophysiological studies agree well with previous observations (3,6,15,16).…”
supporting
confidence: 93%
“…In fact, diminished 1-receptor binding (with no change in affinity) during hypothyroidism has been demonstrated (3,15). In peripheral tissues, parallel changes in adenylate cyclase activity have been reported (16). Our electrophysiological studies agree well with previous observations (3,6,15,16).…”
supporting
confidence: 93%
“…In contrast to hyperthyroidism, however, the means by which adrenergic responsiveness is (38)(39)(40). These results suggest that one mechanism for decreased adrenergic responsiveness in hypothyroidism common to many systems may be a reduction in the number of 8-receptors.…”
Section: Discussionmentioning
confidence: 79%
“…It has been suggested that some of the metabolic abnormalities in thyroid disease may be secondary to alterations in the metabolism of adenosine 3':5'-cyclic monophosphate (cyclic AMP) in tissues (Krishna, Hynie & Brodie, 1968;Levey, Skelton & Epstein, 1969a;Caldwell & Fain, 1971). Investigations of this type have largely been concerned with heart and adipose tissue of experimental animals, although metabolic changes have also been studied in the liver in thyroid disease (Freedland, 1965;Dooner, Parada, Aliaga & Hoyl, 1967;Klion, Segal & Schaffner, 1971).…”
Section: Introductionmentioning
confidence: 99%